The Influence Of Competency Development On Increasing The Capacity Of Civil Apparatus In The Government Of West Nusa Tenggara Province - Riska Aulia; St. Maryam St. Maryam; Lluluk Fadliyanti (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Study This aim For analyze influence age, education, years of service, as well development competencies that include competence technical, competence managerial, competence social cultural and competence government to improvement capacity Apparatus Civil Servants in Government West Nusa Tenggara Province, both in a way partial and simultaneous. The research uses a quantitative approach with a causal associative research type. The research results show that in a way partial development competence managerial and competence social cultural, influential positive and significant to improvement capacity Apparatus Civil Servants. On the other hand, education, age, length of service, and development competence technical No influential significant to improvement capacity Apparatus Civil Servant. In general simultaneously, all variables independent influential significant to improvement capacity Apparatus Civil State. Variables that provide the biggest influence is development competence social cultural research This show that improvement capacity Apparatus Civil Servants do not only influenced by characteristics individuals, such as age, education and length of service , however more determined by development relevant competencies with demands implementation task government.